Didactic strategy for the learning of biogeochemical cycles from transdiscipl inarity - Ruíz Martínez, Alexandra (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This research, of mixed methods, consisted in the implementation of student projects, where the general aim is to demonstrate that the production of projects by students is a more appropriated strategy to restructure preconceptions of the topic of composition of matter and its physicochemical transformation, than those traditional conductive schemes in high-school students. It is an example of daily praxis where education comes into view as an opportunity of finding interdisciplinary approach and a systemic thinking. The theme of the biogeochemical cycles, implemented as projects, is a precise methodological proposal to fructify this opportunity. As for the integration of the subject and the selection of the sample it was made between the so-called hard sciences like Chemistry, with soft disciplines like Biology. Finally, for the implementation, two groups of students of the same grade of secondary education were formed, but with different conditions each other; Then the measuring instrument was performed, pretest and posttest; Then some observations of the field work were recorded and a survey was applied to assess the satisfaction of the project.